Planning sustainable cities : global report on human settlements 2009 - United Nations Human Settlements Programme (London : Earthscan, 2009)
This publication reviews recent urban planning practices and approaches, discusses constraints and conflicts therein, and identifies innovative approaches that are more responsive to current challenges of urbanization. It notes that traditional approaches to urban planning (particularly in developing countries) have largely failed to promote equitable, efficient and sustainable human settlements and to address twenty-first century challenges, including rapid urbanization, shrinking cities and aging, climate change and related disasters, urban sprawl and unplanned peri-urbanization, as well as urbanization of poverty and informality. It concludes that new approaches to planning can only be meaningful, and have a greater chance of succeeding, if they effectively address all of these challenges, are participatory and inclusive, as well as linked to contextual socio-political processes.--Publisher's description.
'UN HABITAT'
Includes bibliographical references (p. [275]-293) and index.
Keywords: City planning -- Environmental aspects; Urban ecology (Sociology).; Sustainable development